THE INFLUENCE OF GENDER, TEOG EXAM SCORES AND SOCIOECONOMIC STATUS ON THE ACCOMPLISHMENT OF STUDENTS REGARDING READING AND INTERPRETATION OF THE FREQUENCY POLYGON AND HISTOGRAM - HALAT, Erdoğan; ÇİMENCİ ATEŞ, Firdevs (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The aim of this current study was to investigate the effects of variables, such as gender, TEOG exam scores and socio-economic status on the 8th grade students about the reading and interpretation of the Frequency Polygon and Histogram. The study included 388 eighth grade students who were from four different middle schools. The researchers used a multiple choice statistics test in the collection of the data. This test contained 22 questions about the reading and interpretation of graphs and finding of the measures of both central tendency and dispersion. This test was developed by the researchers who piloted it and found its reliability of Cronbach's alpha value as 0.80. In the analysis of the data, the researchers used the paired samples t-test, independent samples t-test and two- way ANOVA. The study pointed out that the participants of this study were more successful in reading and interpretation of Frequency Polygon than Histogram. There was no statistically significant difference found with regard to the value of mode in both types of graphs between the achievement levels of the students. However, the study also indicated that the participants were more successful on the items that required the interpretations of standard deviations than the items which required the computation of standard deviations. Moreover, although gender was not a great factor on the accomplishment levels of the participants on the test, both TEOG exam scores and socio-economic status played prominent roles on the students’ achievements on the test. There was a positive relationship between the students’ achievement levels and socio-economic status on the statistics test.